The Effect Of Acute Jamu Kunyit Asam After Strenuous Physical Exercise On Creatine Kinase Levels - Fajar Apollo Sinaga; Rika Nailuvar Sinaga; Mandike Ginting (International Journal of Health and Pharmaceutical (IJHP), 2023)
Strenuous physical exercise can trigger muscle damage causing an increase in creatine kinase levels. One of the strategies to prevent muscle damage is to consume antioxidants and anti-inflammatory. Jamu Kunyit Asam is known to have antioxidant and anti-inflammatory activity. The aim of this study was to determine the effect of acutely giving Jamu Kunyit Asam on creatine kinase levels after strenuous physical exercise. The research sample used 20 trained males. The sample was divided into two groups (Experiment = 10; Placebo = 10). The pre-test was done by checking creatine kinase levels before engaging in strenuous physical exercise. After doing strenuous physical exercise by running on a treadmill with an intensity of 90-100% for 30 minutes, the experimental group was given 250 ml of Jamu Kunyit Asam every day for 3 days, while the control group was given a placebo drink. Creatine kinase levels were measured immediately, 24 hours, 48 hours, and 72 hours after strenuous physical exercise. The results showed that CK levels decreased significantly 24 hours, 48 hours and 72 hours after strenuous physical exercise in the Jamu Kunyit Asam group compared to the placebo group (p<0.05). The conclusion of this study is that giving Jamu Kunyit Asam acutely after doing strenuous physical exercise can reduce creatine kinase levels in trained male athletes. Acute Jamu Kunyit Asam supplementation in this study can help reduce muscle damage due to strenuous physical exercise through nutritional interventions.